Paternal p,p′-DDE exposure and pre-pubertal high-fat diet increases the susceptibility to fertility impairment and sperm Igf2 DMR2 hypo-methylation in male offspring - Liping Lu; Yuzhou Cheng; Wei Wu; Lijun Wang; Shuqi Li; Qianyu Li; Liangjing Chen; Jianyun Zhang; Rong Chen; Xiaohua Tan; Yu Hong; Lei Yang; et al. (Ecotoxicology and Environmental Safety, 2024)
The hypothesis of paternal origins of health and disease (POHaD) indicates that paternal exposure to adverse environment could alter the epigenetic modification in germ line, increasing the disease susceptibility in offspring or even in subsequent generations. p,p′-Dichlorodiphenyldichloroethylene (p,p′-DDE) is an anti-androgenic chemical and male reproductive toxicant. Gestational p,p′-DDE exposure could impair reproductive development and fertility in male offspring. However, the effect of paternal p,p′-DDE exposure on fertility in male offspring remains uncovered. From postnatal day (PND) 35 to 119, male rats (F0) were given 10 mg/body weight (b.w.) p,p′-DDE or corn oil by gavage. Male rats were then mated with the control females to generate male offspring. On PND35, the male offspring were divided into 4 groups according whether to be given the high-fat diet (HF): corn oil treatment with control diet (C-C), p,p′-DDE treatment with control diet (DDE-C), corn oil treatment with high-fat diet (C-HF) or p,p′-DDE treatment with high-fat diet (DDE-HF) for 35 days. Our results indicated that paternal p,p′-DDE exposure did not affect the male fertility of male offspring directly, but decreased sperm quality and induced testicular apoptosis after the high-fat diet treatment. Further analysis demonstrated that paternal exposure to p,p′-DDE and pre-pubertal high-fat diet decreased sperm Igf2 DMR2 methylation and gene expression in male offspring. Hence, paternal exposure to p,p′-DDE and pre-pubertal high-fat diet increases the susceptibility to male fertility impairment and sperm Igf2 DMR2 hypo-methylation in male offspring, posing a significant implication in the disease etiology.